Prussian army in Sieradz (1793–1806) - Włodarczyk, Zdzisław (City and War, 2021)
South Prussia – the province created from the lands seized as a result of the Second Partition of Poland (1793) immediately became an integral part of the Hohenzollern monarchy. Immediately, changes began to be made in the way it was managed, striving to resemble the so-called “Old provinces”. In many cities and towns, smaller or larger military units were located – this also applies to Sieradz. Initially, these were small formations. The outbreak of the Kościuszko Uprising in South Prussia and the successes of the insurgents (including the shortterm capture of Sieradz) made the Prussians aware of the need to strengthen their military presence in the province. After the end of the uprising, the fusilier battalion No. 8 was deployed in the city. Several hundred soldiers were constantly staying here, many of them with families, which had an impact on the ethnic face of the small town. For many years, the atmosphere of mutual relations was enlivened by the conflict between the battalion commander and the city authorities. Baron Franz Leopold von Kloch, upon his arrival in the city, purchased the property that used to belong to the late Mayor Antoni Kwiatkowski. In the opinion of the townspeople it happened without their rights, because due to his debts, the house became the property of Sieradz. The magistrate took legal action, and the whole matter was not completed until 1816. The highest factors, including the king himself, were interested in the course and results of the dispute. The departure of most of the army to the war with Napoleonic France (1806) ended the stay of the fusiliers in Sieradz.